Low-cost adsorbents for environmental pollution control: a concise systematic review from the prospective of principles, mechanism and their applications. Issue 11 (1st September 2022) - Tony, Maha A.
Abstract: Nowadays, water scarcity is an identifiable problem facing society. However, as a result of modernization, water consumption is dramatically in increase although the water supply remains constant. Unfortunately every sector consumes water resulting in massive amounts of wastewater that requires treatment prior to their final disposal that still a challenge to the modern societies. Among the various technologies investigated, adsorption considered the most widely applied technology for safe environmental remediation. In this regard, the term of green adsorbents is introduced that is meant the low-cost materials originated from waste, i.e., agriculture waste to be valuable adsorbents. Thus, extensive list of different adsorbents from natural, industrial waste, agriculture bio-products or modified materials have been applied for the elimination of various contaminants from aqueous matrix are compiled here as a demanding area since it has double benefits as an industrial ecology approach. Also, this article discusses the basic principles of adsorption process including the adsorption isotherm and kinetic models. Although numerous review articles are dealing with low-cost adsorption performances, there is insufficient information on the emerging pollutants elimination. The major focus of this work is highlighting the research on the application of the low-cost adsorbents on the emerging pollutants, namely, pharmaceuticals, pesticides, personal care products and perfluorinated compounds. Scattered information on using various adsorbents are provided information in adsorbing emerging pollutants uptake reached to 920 mg/g. The main parameters that affect the adsorption process and the economic prospective is also discussed. Desorption and recycling scenario is concluded and desorption efficiency could reach to 99%. Finally, the future development of further research and few suggestions are also prospected. Graphical Abstract: UF0001